2017
DOI: 10.1007/s00404-017-4352-6
|View full text |Cite
|
Sign up to set email alerts
|

The incidence of and risk factors for a repeat obstetric anal sphincter injury (OASIS) in the vaginal birth subsequent to a first episode of OASIS: a hospital-based cohort study

Abstract: We found that 8.4% of women sustained a repeat OASIS in a subsequent vaginal birth with this risk being associated with the presence of a short second labour and certain features from the first labour.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
35
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(36 citation statements)
references
References 24 publications
1
35
0
Order By: Relevance
“…The following vaginal delivery rate of 67% (versus approximately 95% for multiparous women in general) [16] is not unexpected given the ongoing morbidity experienced. An 8.8% rate of repeat OASI is in keeping with the literature, with Antonakou et al [17] reporting rates of 8.4%. These rates should be disclosed when counseling women on subsequent birth choices, the reality being that for one in ten of the women surveyed, they decided to have no further children because of their OASI.…”
Section: Discussionsupporting
confidence: 84%
“…The following vaginal delivery rate of 67% (versus approximately 95% for multiparous women in general) [16] is not unexpected given the ongoing morbidity experienced. An 8.8% rate of repeat OASI is in keeping with the literature, with Antonakou et al [17] reporting rates of 8.4%. These rates should be disclosed when counseling women on subsequent birth choices, the reality being that for one in ten of the women surveyed, they decided to have no further children because of their OASI.…”
Section: Discussionsupporting
confidence: 84%
“…While the impact of episiotomy on the index delivery was investigated [2, 8], to the best of our knowledge, our study is the largest to investigate whether episiotomy in the index delivery influence the delivery and labor outcomes on subsequent delivery. Antonakou et al found that women who had an episiotomy at first vaginal birth had an almost fourfold increased risk of repeat obstetric anal sphincter injury in a second vaginal birth [13]. …”
Section: Discussionmentioning
confidence: 99%
“…Women with a previous OASIS were excluded from this study as the literature reports a fivefold increased risk of recurrence of severe perineal trauma in these cases. [19][20][21] This means that any OASIS would most likely be due to the prior OASIS and not by any exposures during birth.…”
Section: Methodsmentioning
confidence: 99%